Comparison of Prediction of the Number of People Exposed to Covid 19 Using the Lagrange Interpolation Method with the Newton Gregory Maju Polynomial Interpolation Method - F. Anthon Pangruruk; Simon P. Barus (Formosa Journal of Applied Sciences, 2023)
In March 2020 the World Health Organization stated that the Corona Virus pandemic (Covid-19) was due to its massive spread and hit all countries in the world. Academics and practitioners are called upon to carry out research activities in order to obtain a mathematical model that can be used to predict the number of people exposed to Covid-19 or other diseases. The researchers previously tried research to predict the number of people exposed to Covid-19 from early 2021 using the Monte Karlo method, the Hybrid Nonlinear Regression Logistic– Double Exponential Smoothing method, the Arima method, the BackPropagation and Fuzzy Tsukamoto methods, the K-Nearest method. Neighbors, Time Series Analysis method, Winter Method and Long Short Time Memory (LSTM) Artificial Neural Network method.